2012
DOI: 10.1021/ma300706k
|View full text |Cite
|
Sign up to set email alerts
|

Processing–Morphology–Property Relationships and Composite Theory Analysis of Reduced Graphene Oxide/Natural Rubber Nanocomposites

Abstract: Dispersion of reduced graphene oxide (RG-O) into natural rubber (NR) was found to dramatically enhance the mechanical, electrical, and thermal properties of NR. However, property improvements were strongly dependent upon the processing history and nanocomposite morphology. Cocoagulating a stable RG-O suspension with NR latex afforded a weblike morphology consisting of platelet networks between the latex particles, while two-roll mill processing broke down this structure, yielding a homogeneous and improved dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
239
3
9

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 327 publications
(257 citation statements)
references
References 49 publications
6
239
3
9
Order By: Relevance
“…The layers of graphene-based materials are expected like in layered silicates, to be separated from each other in water and to be mixed uniformly with the rubber latex particles. The latex mixing and co-coagulation process has been applied by Zhan et al [25] then by Potts et al [26] for the preparation of reduced graphene oxide/natural rubber nanocomposites.…”
Section: Manufacturing Techniques Of Rubber Nanocompositesmentioning
confidence: 99%
“…The layers of graphene-based materials are expected like in layered silicates, to be separated from each other in water and to be mixed uniformly with the rubber latex particles. The latex mixing and co-coagulation process has been applied by Zhan et al [25] then by Potts et al [26] for the preparation of reduced graphene oxide/natural rubber nanocomposites.…”
Section: Manufacturing Techniques Of Rubber Nanocompositesmentioning
confidence: 99%
“…In this study, only the version for unidirectional alignment is considered since the microstructural analysis demonstrated that reinforcements are preferentially aligned [6]. Another analytical model, by Tandon and Weng (TW), which was derived from the MT method [17], is also used in the literature for calculation of the Young's modulus of graphenereinforced nanocomposites [9,18,19]. Hui and Shia (HS) obtained simple closed-form expressions based on the TW method [20]; their method can be used to implement the MT approach in prediction of the elasticity modulus of graphene-nanocomposites [21].…”
Section: Introductionmentioning
confidence: 99%
“…stacked, intercalated and exfoliated [18]. Graphene or GO flakes with a stacked morphology are characterized by presence of more than several sheets.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a method to inhibit the surface oxidation is urgently required. Graphene is capable of both scavenging free-radicals [15][16][17][18] and can serving as gas barriers [19][20][21][22][23], these dual effects make graphene be effective in improving oxidation stability of Bi 2 Se 3 . In this study, we fabricated high-quality G-Bi 2 Se 3 -G heterostructure via CVD.…”
Section: Introductionmentioning
confidence: 99%